Lápices y rosas. Un análisis comparativo de dos películas históricas sobre el pasado traumático argentino y español - Malena Corte (Centre de Recherches sur les Mondes Américains, 2014)
After traumatic events happen, part of the film industry usually represents facts of that recent past, sometimes through documentaries, sometimes through historical fiction cinema.The proposal of this present work is to make a comparative analysis between the argentine film La noche de los lápices and the spanish film Las trece rosas. Our interest is not to utilize these films to compare the presented historical periods (in the first case, the last military dictatorship in Argentina; in the second one, Franco’s dictatorship in Spain), but to observe the way both pictures build a memory about that traumatic dictatorial past.In concrete, we think historical films usually indicate us more about issues concerning the period these films were made in, rather than those concerning the specific moment involved in the representation. The main hypothesis which will guide this work considers that even if both movies represent different historical moments and, at the same time, are made in also different contexts, it is possible to compare them given the fact that they both aim to a memory construction and a past traumatic events representation where the common axis seems to be the representation of the victims in an innocent way, relegating their political identities to a second place.